Tool management in flexible manufacturing systems - Gemici, Deniz Gökçe (My University, 2000)
The scope of this thesis is to provide another approach in tool issue strategies in tool management systems (TMS) within flexible manufacturing system environments. Tool Management is the organisation of the flow of tools in the system to match the work-piece flow, such that the right tools are available in the right place, at the right time to allow processing of the parts by the machine. In order to accomplish this, there is a need of a compatible tool issue strategy applied in the system. There are two types of tool issue strategies: work-piece-oriented and tool-oriented strategies. In the work-piece oriented strategies, the number and type of tools are determined from the machining requirements of a work-piece spectrum introduced over a given scheduling period. Unlike work-piece oriented strategies, tool issue strategies are targeted to respond to the need for work-piece processing and routing flexibility and in situations where there are many diverse work-pieces produced. This study mainly covers the tool-oriented strategies and simulations are performed with one of the tool-oriented strategies as well. In this study, first the literature about flexible manufacturing systems and as a part of it, tool management systems (TMS) are reviewed. Furthermore, the tool management system with tool oriented strategies are comprehensively studied and full clustering tool-oriented strategy is focused. Related to this part of the study, an illustrative example is shown with an Excel macro, developed for this study. Eventually, the results are interpreted and the report is concluded with the suggestions for the future studies in this area.

Bu tezin amaci esnek imalat sistemlerindeki takim yonetim stratejilerine yeni bir bakis acisi saglamaktir. Takim Yonetimi, imalat sistemi icerisindeki takimlarin parca akisiyla uyumlu bir sekilde calismasidir. Bu sayede, dogru takimlar dogru yerde ve de dogru zamanda parca isleme operasyonlari icin hazir bulunurlar. Sistemin etkin bir sekilde calismasi icin uygun bir takim stratejisine ihtiyac vardir. Takim yonetimi stratejilerinde iki cesit strateji vardir: parca bazli, takim bazli stratejiler. Parca bazli stratejiler takim miktari ve cesitlerinin parca bazinda makina ihtiyaclarina gore secildigi sistemler icin gereklidir. Parca bazli stratejilerin tersine, takim bazli stratejiler parca isleme ve operasyon esnekligi gerektiren, cok sayida farkli karakteristige sahip parcalarin uretildigi durumlarda etkindir. Bu calisma sadece takim bazli stratejileri uzerinde yogunlasacak ve simulasyonlar takim bazli stratejilerden tam gruplama stratejisi ile yapilacaktir. Bu calismada esnek imalat sistemleri, ve de bir parcasi olan takim yonetim sistemleri ile ilgili literatur gozden gecirilecektir. Takim yonetimi ve stratejileri incelenecek, ve takim bazli stratejilerden tam gruplama stratejisi detayli bir sekilde calisilacaktir. Bu strateji ile ilgili bir ornek gelistirilen Excel macro ile gosterilecektir. Sonuclar tartisilacak ve bu alandaki ileri calismalar icin onerilerde bulunulacaktir.
Keywords: Genel yönetim; İmalat; Üretim yönetimi